Evaluation of Performace of Different Varieties of Potato (Sonalum tuberosum L.) in Bajhang, Nepal - Saroj Thapa (Hasanuddin University, 2022)
A study to Evaluate the performance of different varieties of potato was conducted in Daulichaur, Bajhang from February to June, 2021. Six commonly grown potato varieties namely Cardinal, Janakdev, Khumal rato-2, Khumal Ujjwol, MS 42.3 and Bajhang local were used for the study. An experiment was conducted in Randomized Complete Block Design (RCBD) with 6 treatments replicating 4 times each. The data on plant height, number of main stems per hill, number of leaves, and canopy diameter were taken at different days after planting (DAP) and the data on number and weight of tubers were taken after harvesting of potato. Data entry and analysis was done in MS-Excel and R-Studio. Significant variation among the varieties in terms of plant height, main stem per hill, canopy diameter and leaves number per plant was observed. Number of stems per hill was found maximum (3.88) and minimum (1.63) on Bajhang local and Janakdev respectively. Plant height is found maximum on Janakdev (42.75 cm) and minimum on Khumal rato-2 (21.45 cm). The maximum (40.90) and minimum (27.55) number of leaves per plant was recorded on Khumal Ujjwol and Cardinal while maximum and minimum canopy diameter was observed on Bajhang local (40.90 cm) and Khumal rato-2 (36.12 cm). Similarly, yield and all the yield attributing parameters was found significant at 5% level of significance. Highest number of tuber per plant was observed on Bajhang local (17.25) and lowest number of tuber per plant was observed on Khumal rato-2 (8.25) in which highest number of marketable size tuber per plant (>25g) was recorded on Khumal Ujjwol (12.05) and lowest number of marketable size tuber per plant (<25g) was recorded on Khumal rato-2 (5.75) but variation among the varieties in case of unmarketable tuber per plant was non-significant. Highest tuber weight per plant (485.50g) and lowest tuber weight per plant (306.25g) was recorded from Khumal Ujjwol and MS 42.3 respectively. The highest tuber yield was recorded from Khumal Ujjwol (40.45 t/ha) and lowest from MS 42.3 (25.52 t/ha).